RESPONS EMPAT KULTIVAR PADI GOGO (Oryza sativa L.) TERHADAP KADAR LENGAS TANAH YANG BERBEDA - Sukma, Peggi Melati; Samudin, Sakka; Fathurrahman, Fathurrahman (AGROTEKBIS, 2019)
The need for rice as one of the main food sources of the Indonesian population continues to increase in line with the increase of population with a rate of 2% per year. The objective of this research is to know the response of four cultivars of upland rice to different soil moisture content, drought resistant cultivars and water content where cultivars are difficult or can not grow. The research was conducted at Green House Agrotechnology, Faculty of Agriculture, Tadulako University of Palu. From March to June 2017. This research was prepared using Completely Randomized Design (CRD) two factors consisting of local rice cultivar as first factor that is Cultivar Tagolu, Cultivar Habo, Uva Buya Cultivar and Cultivar Dongan. While Soil Humidity Level as the second factor soil moisture level 100%, 75%, 50% and 25%. The results showed that the Habo cultivar and Dongan cultivars have long and wider leaves, the number of grains contained, the number of tillers, the number of leaves, and the weight of 1000 grains better compared to other cultivars. At 75% and 50% soil moisture levels can still grow crops well compared to 25% moisture level. The influence of soil moisture level is similar in all cultivars.